2012
DOI: 10.1037/a0027106
|View full text |Cite
|
Sign up to set email alerts
|

Is it the exception or the rule? Daily co-occurrence of physical, sexual, and psychological partner violence in a 90-day study of substance-using, community women.

Abstract: Objective This study aims to describe the daily co-occurrence of physical, sexual, and psychological intimate partner violence (IPV) among substance-using, community-based women currently experiencing IPV. Methods A micro-longitudinal study design was used to collect data daily from 49 women for 90 days. Results On the majority of days (62%), no IPV occurred; 27% of days were characterized by psychological IPV alone, followed by the co-occurrence of psychological and physical IPV (6% of IPV days). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 55 publications
9
72
0
1
Order By: Relevance
“…Partner reports of alcohol use and dating violence were not obtained; future research would be improved by including both dyad members. Although similar to that obtained in other 90-day daily diary research (Sullivan et al, 2012), our daily diary compliance rate was somewhat low. Reactivity to assessment is a concern given the length of the daily assessments and findings that the number of surveys completed was inversely associated with physical and sexual aggression.…”
Section: Discussionmentioning
confidence: 66%
“…Partner reports of alcohol use and dating violence were not obtained; future research would be improved by including both dyad members. Although similar to that obtained in other 90-day daily diary research (Sullivan et al, 2012), our daily diary compliance rate was somewhat low. Reactivity to assessment is a concern given the length of the daily assessments and findings that the number of surveys completed was inversely associated with physical and sexual aggression.…”
Section: Discussionmentioning
confidence: 66%
“…Probably, the best known case is IPV, which typically involves both psychological and physical aggression, and not infrequently involves sexual aggression and stalking by the intimate partner as well (Krebs et al 2011;Straus et al 1996). The most recent data reveal that these interconnections even operate on a daily level; in one study, physical IPV was 64 times more likely on a day when psychological IPV had occurred (Sullivan et al 2012). More generally, a nationally representative survey of Latino women found that nearly two-thirds (63 %) of victimized women reported more than one type of victimization (Cuevas et al 2010), with a mixed pattern of polyvictimization and revictimization being the most commonly reported pattern (multiple victimization types in childhood and/or adulthood with at least one type experienced more than once).…”
Section: Poly-victimization: Co-occurrence Among Forms Of Victimizationmentioning
confidence: 96%
“…A very small proportion of our sample used more severe forms of sexual IPV. Based on previous studies documenting that the incidence and chronicity of sexual IPV is typically less than that of psychological and physical IPV (Jaquier, Hellmuth, & Sullivan, 2012;Pico-Alfonso, 2006;Sullivan et al, 2012), it is expected that sexual IPV would be less prevalent in this sample compared to other types of IPV. Because sexual IPV perpetration among pregnant women has not been examined prior to our study, and because sexual IPV victimization among men whose female partners are pregnant has never been investigated to our knowledge, the findings of this exploratory study may facilitate future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither of these studies examined women's sexual IPV perpetration. Finally, in the general population, sexual IPV victimization frequently co-occurs with psychological and physical IPV victimization (Hines & Saudino, 2003;Logan, Cole, & Shannon, 2007;Sullivan, McPartland, Armeli, Jaquier, & Tennen, 2012). However, research has not yet examined the extent to which various types of IPV victimization and perpetration (i.e.…”
mentioning
confidence: 99%